2009
DOI: 10.2193/2008-250
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Rice as Food of Waterfowl Wintering in the Mississippi Alluvial Valley

Abstract: Waterfowl habitat conservation strategies in the Mississippi Alluvial Valley (MAV) and several other wintering areas assume carrying capacity is limited by available food, and increasing food resources is an effective conservation goal. Because existing research on winter food abundance and depletion is insufficient to test this hypothesis, we used harvested rice fields as model foraging habitats to determine if waste rice seed is depleted before spring migration. We sampled rice fields (n = 39 [winter 2000–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 34 publications
(43 reference statements)
3
64
1
Order By: Relevance
“…Eadie et al (2008) and Remsen et al (1991) reported that 15 species of waterfowl regularly used rice fields during the non-growing season in California and the Gulf Coast, USA, whereas at least nine species were commonly observed in MAV fields (Delnicki and Reinecke 1986;Reinecke et al 1992;Twedt and Nelms 1999;Huner et al 2002;Greer et al 2009). Additionally, authors have reported that waterfowl using rice fields in winter feed heavily on waste rice (Singleton 1951;Reinecke et al 1989;Miller and Newton 1999;Dabbert and Martin 2000;van Groenigen et al 2003;Manley et al 2004;Mugica et al 2006a;Greer et al 2009). …”
Section: Rice Seedsmentioning
confidence: 99%
“…Eadie et al (2008) and Remsen et al (1991) reported that 15 species of waterfowl regularly used rice fields during the non-growing season in California and the Gulf Coast, USA, whereas at least nine species were commonly observed in MAV fields (Delnicki and Reinecke 1986;Reinecke et al 1992;Twedt and Nelms 1999;Huner et al 2002;Greer et al 2009). Additionally, authors have reported that waterfowl using rice fields in winter feed heavily on waste rice (Singleton 1951;Reinecke et al 1989;Miller and Newton 1999;Dabbert and Martin 2000;van Groenigen et al 2003;Manley et al 2004;Mugica et al 2006a;Greer et al 2009). …”
Section: Rice Seedsmentioning
confidence: 99%
“…More recent studies in Spain have shown that similarly crushed and flooded fields have a waste rice density of 24.5 g m -2 (Toral 2011), while in North America the values range from 6.6 to 67.2 g m -2 (Stafford et al 2010). In any case, we found an abundance of seeds well above the giving-up density of 5 g m -2 , under which waterfowl are considered to cease foraging (Reinecke et al 1989;Greer et al 2009). Therefore, ducks should have considered the experimental plots as a valuable feeding habitat.…”
Section: Discussionmentioning
confidence: 45%
“…It has been demonstrated that winter flooding is highly effective in controlling some weeds such as weedy rice (Oryza sativa L., Fogliatto et al 2010) and in inhibiting dormancy break of other seeds such as the exotic Heteranthera limosa (Baskin et al 2002). Greer et al (2009) attributed 44-47 % of waste rice seed loss over the winter to deterioration due to flooded conditions. Another factor of seed bank decrease may potentially be waterfowl foraging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used an average true metabolizable energy content for waterfowl foods of 1.55 kcal/g to back-calculate an average kg/ha over our entire study site (outliers-removed data). Our high (mean þ 1 SE) estimate of food availability roughly equates to 112 kg/ha, which is below the observed foraging threshold in many other systems (Naylor 2002;Greer et al 2009;Hagy and Kaminski 2012). Simply stated, the threshold at which ducks cannot (or will not) forage (profitably) could appear as a horizontal line anywhere on Figure 4.…”
Section: Discussionmentioning
confidence: 56%